Influence of mix design parameters on restrained shrinkage cracking in non-structural concrete patch repair mortars - Arito, Philemon (Concrete Materials and Structural Integrity Research Unit (CoMSIRU), 2018)
There is a dearth of clear and consistent information on the effects of mix design parameters, and their corresponding interactions, on restrained shrinkage cracking in non-structural concrete patch repair mortars (PRMs). This dearth of information makes the design and development of PRMs with improved resistance to cracking challenging. The problem is further compounded by the fact that the existing code of practice for concrete repair - the EN 1504-3:2005 - specifies many material properties such as chloride ion content, compressive strength, bond strength, skid resistance and capillary absorption. Some of these material properties, such as skid resistance and chloride ion content, are not relevant to cracking. Also, empirical analytical models for predicting stresses and the age at cracking in PRMs need improvement to accommodate recent developments in materials such as admixtures and additives. Accurate prediction models help design engineers make informed choices during the selection of PRMs. The principal objective of this study was to generate new knowledge that would inform the design of non-structural PRMs and the development of performance requirements for these PRMs. This was accomplished through an investigation into the influence of multiple mix design parameters and crack-determining material properties on restrained shrinkage cracking, involving a critical review of literature and a comprehensive laboratory experimental programme. The experimental work was organised into two phases. Phase one entailed an investigation into the effect of water content, binder content, binder type, curing type, shrinkage reducing admixture (SRA) dosage, polymer type and polymer content on cracking. A 2⁵ full factorial experiment approach with three replicates was used in this phase. 32 mixes were studied. The sensitivity of cracking to the listed mix design parameters was determined with respect to the age at cracking in ring specimens made in accordance with ASTM C 1581. A trend analysis of the investigated mix design parameters and cracking was also done.